2014
DOI: 10.1590/0034-7167.2014670518
|View full text |Cite
|
Sign up to set email alerts
|

Acesso ao cuidado à saúde da criança em serviços de atenção primária

Abstract: It was conducted a qualitative study based on the methodological framework of dialectical hermeneutics, aiming to identify the attribute access from primary care to solve the health problems of children under one year old from the reports of parents and caregivers. Sixteen caregivers of children were involved, all of them seen in the emergency units of Cascavel-PR, in 2010. Four thematic categories were recognized: Family counselling in seeking health care for the child; Absence of reception on the first conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 12 publications
1
14
0
18
Order By: Relevance
“…In the results, the perception of family caregivers regarding the role of PHC was not in line with the guidelines of the network, whose objective is to strengthen the actions of primary care services as a care coordinator, aiming to guarantee the continuous care and the strengthening of bonds between professionals, families and health institutions (11) . However, similar results have also been found in other studies, emphasizing that emergency services and tertiary services are preferred at the expense of primary level services, even to address the demands of PHC (8,12,28) . According to a Chilean study, when the attention to the health of CSHCN is focused on secondary and tertiary care services financial costs increase, the continuity of care is impaired and the accessibility to the benefits available in primary health care is restricted (30) .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the results, the perception of family caregivers regarding the role of PHC was not in line with the guidelines of the network, whose objective is to strengthen the actions of primary care services as a care coordinator, aiming to guarantee the continuous care and the strengthening of bonds between professionals, families and health institutions (11) . However, similar results have also been found in other studies, emphasizing that emergency services and tertiary services are preferred at the expense of primary level services, even to address the demands of PHC (8,12,28) . According to a Chilean study, when the attention to the health of CSHCN is focused on secondary and tertiary care services financial costs increase, the continuity of care is impaired and the accessibility to the benefits available in primary health care is restricted (30) .…”
Section: Discussionsupporting
confidence: 87%
“…Another relevant aspect refers to geographical barriers; thus, when the specialized service is distant, service functionality is impaired (12) . A systematic review of 61 articles on barriers to access to health services has shown that the coverage of health care is adversely affected by transport-related barriers, particularly for lower-income households (29) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk classification is an important tool identified by the family groups to optimize priority access 18 . However, as evidenced, the service is limited to a sign of severity and excludes from attendance children with other signs that would also require immediate care.…”
Section: Acknowledgmentsmentioning
confidence: 99%